Determination of Cd, Cu, Fe, Mn, Ni and Zn in Antarctic Sea water - Comparison of electrochemical and spectroscopic procedures - ABOLLINO, Ornella; ACETO, Maurizio; SARZANINI, Corrado; MENTASTI, Edoardo; G. Sacchero (1995)
Different procedures for the determination of ultratrace metal ions in Antarctic sea water have been adopted and critically compared. The investigated metal ions were Cd, Cu, Fe, Mn, Ni and Zn. Sea water samples were analysed with adsorptive cathodic stripping voltammetry and with graphite furnace atomic absorption spectroscopy. Different treatments, such as UV irradiation, acidification and on-line sample enrichment were adopted and the results for samples collected in different sites and on a vertical profile were discussed and compared.